Wyjątki od zasady dostępu do informacji publicznej w Stanach Zjednoczonych na przykładzie sprawy Milner v. Department of the Navy - Kuźnicka, Dominika (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
This article applies to restrictions on access to public information in Poland and in the United States. Access to public information is one of the elements of broadly defined right to information. In modern constitutions of democratic countries alongside traditional political rights and freedoms it is more frequently mentioned right to obtain information from public authorities. American bill- Freedom of Information Act- provides everyone access to the information created by federal authorities and includes 9 exemptions from general rule of transparency. Based on the breakthrough in this field Supreme Court ruling on Milner v. Deparment of the Navy case author is trying to bring the issue of bases and restrictions on access to public information in the United States. The second part of the work is dedicated to the restrictions on the right of access to public information in Poland. Relying on the professional literature and a series of court rulings author made an attempt to examine what judgment could be adopted in a similar case on the basis of Polish legal regulations. A summary of the article was devoted entirely to the comparative analysis of regulations on access to public information in Poland and the USA.
Keywords: information; exemptions; high 2 exemption; Public information